Influence of the size of soursop seed granules on the mechanical and water properties of compressed earth bricks - Kouame, Alfred Niamien; Ouedraogo, Moussa; Manouan, Wedjers Max Robin; Kouakou, Lebe Prisca Marie-Sandrine; Meite, Namory; Doubi, Bi Irie Herve Goure; Zokou, Esmel Privat Zokobadi; Konan, Leon Koffi (International Journal of Chemistry and Materials Research, 2023)
The use of plant raw materials in Compressed Earth Bricks has become an increasingly a common practice. This present work is part of this approach; it aims to study the impact of the size of soursop seed granules on the mechanical and water properties of Compressed Earth Bricks (CEB). To do this, clay named Aga from Gagnoa consisting essentially of quartz (77.13 wt%) and clay minerals kaolinite and illite (21.28 wt%) and soursop seeds of fine particle size (d≤0.5 mm) and average (0.5<d<1mm) were used. The results of the mechanical tests showed a drop in compressive strength of 37% and 44% respectively for the formulations with fine granules and medium granules compared to the resistance of the formulation with raw clay. The formulation with fine granules (A94GF6) therefore presents the best compressive strength (3.58 MPa). In terms of water absorption by capillarity, the formulation with fine granules has greater absorption with an absorption coefficient of 0.2824 kg.m-2s-1/2 compared to the formulation with medium granules in which their absorption coefficient is 0.1143 kg.m-2s-1/2. All the results showed that seed granules can be used in compressed Earth Bricks, however it is recommended to use them with a fine particle size (d ≤ 0.5 mm).